2009
DOI: 10.1242/jcs.046276
|View full text |Cite
|
Sign up to set email alerts
|

Growth arrest induces primary-cilium formation and sensitizes IGF-1-receptor signaling during differentiation induction of 3T3-L1 preadipocytes

Abstract: The first stage of 3T3-L1 adipocyte differentiation is growth arrest, which is achieved by contact inhibition at confluence. In growth-arrested confluent 3T3-L1 preadipocytes, α-tubulin acetylation and primary-cilium formation were induced. The blockade of primary-cilium formation by suppressing IFT88 or Kif3a inhibited 3T3-L1 adipocyte differentiation. IGF-1 (IGF-I)-receptor signaling, which is essential for differentiation induction, was sensitized by the formation of a primary cilium in confluent 3T3-L1 pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(156 citation statements)
references
References 30 publications
12
144
0
Order By: Relevance
“…As a control for specificity of recruitment, we expressed epitope-tagged IGF1 Receptor (IGF1R) in the same bcell line. Ciliary IGF1R localization has been observed in differentiating adipocytes 36 ; under our experimental conditions, we did not observe IGF1R localization to the cilium (data not shown). Although there are numerous examples of ciliary membrane components that-when heterologously expressedstill localize to the ciliary membrane, our observation implies that, in the MIN6m9 cell line, sorting to the ciliary membrane compartment is tightly controlled even when potential ciliary components are overexpressed.…”
Section: Disruption Of Basal Body Integrity Impairs Insulin Secretionmentioning
confidence: 41%
“…As a control for specificity of recruitment, we expressed epitope-tagged IGF1 Receptor (IGF1R) in the same bcell line. Ciliary IGF1R localization has been observed in differentiating adipocytes 36 ; under our experimental conditions, we did not observe IGF1R localization to the cilium (data not shown). Although there are numerous examples of ciliary membrane components that-when heterologously expressedstill localize to the ciliary membrane, our observation implies that, in the MIN6m9 cell line, sorting to the ciliary membrane compartment is tightly controlled even when potential ciliary components are overexpressed.…”
Section: Disruption Of Basal Body Integrity Impairs Insulin Secretionmentioning
confidence: 41%
“…Adipogenic differentiation and fat accumulation is associated with transient formation of the primary cilium, containing Wnt and Hh signaling components, such that adipocytes in culture derived from dermal fibroblasts of individuals with Bardet-Biedl syndrome exhibit a higher predisposition for fat accumulation and a higher secreted leptin level than control cells (Marion et al, 2009). Zhu and colleagues demonstrated that the primary cilium and its basal body form an organized signaling pathway for the IGF-1 receptor to induce adipocyte differentiation in confluent 3T3-L1 preadipocytes (Zhu et al, 2009). In addition, childhood obesity and type II diabetes in Alström syndrome patients is caused by mutations in Alström syndrome 1 protein (ALMS1), which localizes to the base of primary cilia (Hearn et al, 2005) and is regulated during adipogenesis (Romano et al, 2008).…”
Section: Primary Cilia In Adult Tissuesmentioning
confidence: 99%
“…Akt is phosphorylated during mitosis and is present in the centrosome and basal body (Wakefield et al , 2003; Zhu et al , 2009). Therefore, we next examined whether INVS might be a direct substrate of Akt.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, PDGFRα signaling in the primary cilium regulates fibroblast migration via Akt signaling (Schneider et al , 2005; Clement et al , 2013b). Primary cilia organize and extend from the basal body (from the mother centriole) where activated Akt is constitutively present (Zhu  et al , 2009), suggesting that Akt may be involved in ciliary development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation